Introduction to global energy issues - Gicquel, Renaud; Gicquel, May. (Boca Raton : CRC Press, 2013)
'This book seeks to provide a basis for reflection on energy at a global level. It synthesizes the main energy-related issues and requires no specialist knowledge, either of economics, engineering sciences or international relations. It comprises four main chapters, that discuss the major energy sectors (oil, natural gas, coal, synthetic hydrocarbons, electricity, renewable energy), the impacts of energy at macro-economic level, geopolitics and new issues related to energy, notably environmental aspects and successes of demand management policies. The book is aimed at industry professionals, (under)graduate students / academics, economists and policy-makers in the energy sector/field'--
Translation of: Introduction aux probles {u296E}ergiques globaux / Renaud Gicquel. 1992.
Includes bibliographical references and index.
Keywords: Power resources; Energy policy